2013
DOI: 10.1097/bpo.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

Submuscular Bridge Plating for Length-Unstable, Pediatric Femur Fractures

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Studies showed that submuscular plating is an effective alternative for the treatment of fractures of unstable length. 4,6,28,29 Samora et al 6 found that submuscular plating produced excellent healing rates, low complication rates, and early return to weight bearing, with mean time to full weight bearing of 7.8 weeks. Similar results were shown in previous series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that submuscular plating is an effective alternative for the treatment of fractures of unstable length. 4,6,28,29 Samora et al 6 found that submuscular plating produced excellent healing rates, low complication rates, and early return to weight bearing, with mean time to full weight bearing of 7.8 weeks. Similar results were shown in previous series.…”
Section: Discussionmentioning
confidence: 99%
“…Each surgeon used all 3 techniques, including submuscular plating, retrograde flexible intramedullary nailing, and rigid intramedullary nailing. Anterior bowed femoral locking plates (Synthes, West Chester, Pennsylvania; Smith & Nephew, Andover, Massachusetts; and OrthoPediatrics, Warsaw, Indiana) measuring 3.5 and 4.5 mm were used, and the procedure was performed with the 2-incision technique described by Samora et al 6 The surgical techniques for flexible and rigid trochanteric entry and antegrade nailing were described previously. All flexible nail procedures were performed with a retrograde technique with titanium elastic nails (Synthes) (30 procedures) or flexible stainless steel Enders rods (Smith & Nephew, Memphis, Tennessee) (31 procedures) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Time to full weight bearing has been used as another outcome measure, reported at an average of 8 weeks for compression plating, 7 weeks for submuscular plating, and 12 weeks for flexible nailing [4,12]. However, postoperative weight bearing protocols vary widely between providers and institutions, with some allowing immediate weight bearing with assistive device, others requiring touchdown weight bearing until callus formation, with progressive advancement, and others still preferring non-weight bearing until callus formation [5,[7][8][9][10][11]15].…”
Section: Resultsmentioning
confidence: 99%
“…Though several studies demonstrate consistency in healing time and clinical outcomes between these different fixation methods, postoperative weight bearing protocols vary widely between providers, with some requiring non-weight bearing until evidence of radiographic healing, others allowing touchdown weight bearing for 6 weeks with progressive advancement thereafter, and some even further immobilizing in spica casts [4][5][6][7][8][9][10][11][12]. Periods of weight bearing protected by assistive device also vary depending on surgeon preferences [13].…”
Section: Structionsmentioning
confidence: 99%
“…In the series of comminuted shaft femur published by Samora et al ., union time in weeks showed a standard deviation of 2.27. 11 Taking this value of standard deviation as baseline, α = 0.05, β = 0.1, and effect size of 2.5, the sample size required to give a statistical power of 90% was found to be 35 (18 in Group A and 17 in Group B). Hence, the authors started the investigation with 19 individuals in each group.…”
Section: Methodsmentioning
confidence: 99%